EFEKTIVITAS PENDIDIKAN MAJELIS TAKLIM KONVERSI DINIYAH (MTKD) KOTA BANDUNG - Jaenal Abidin; Acep Nurlaeli; Ilham Fahmi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
Existence Majelis Taklim which is almost is in every remote regions should be optimized the role and majerial in order to be able to generate the good graduates. Diniyah convertion majelis taklim present as an renewal in Majelis Taklim. The aim of this study is to describe and  study how  effectiveness implementation of education in Bandung Diniyah Convertion Majelis Taklim. The method of study which is used is qualitative method with phenomenology approach. The technique of collecting data was obtained with observation, interview and documentation. The result of this study is implementation of education Diniyah convertion majelis taklim (MTKD) is started  with planning makes syllabus, the noted of study matter and study contact, systematic schedule, partition muddaris/muddarisah, choosing study matter, method and learning media. Concerning the result which is riched, those are able to generate santri who has science, skill, religious and generate somebody who expert about giving religious spiritual ritual services to public. The support factor of implementation MTKD is collaborate between municipality, Ministry of religion, and mosque keeper. Enthusiasm from santri,  mudarris/mudarrisah which is professional and has high comitment. Furthermore, the resistor factor has not own classroom and less implementation budget of MTKD.